Traditional knowledge on ethno-veterinary and fodder plants in South Angola: an ethnobotanic field survey in Mopane woodlands in Bibala, Namibe province - Bruschi, Piero; Urso, Valeria; Solazzo, David; Tonini, Matteo; Signorini, Maria Adele (Journal of Agriculture and Environment for International Development (JAEID), 2017)
Livestock is a critical resource to improve income and household livelihoods in many rural areas. To date, very few studies have investigated farmers’ local knowledge on plants used in managing animal health and welfare in Angolan Mopane woodland. This is a very dry ecosystem where animal husbandry (mostly cattle and goats breeding) is highly widespread and is often the main form of subsidence, greatly contributing to local communities food security, especially in periods of resources shortage. An ethnobotanical research project was carried out in Bibala (Namibe province – Angola) in 2010 – 2012, in order to collect information on different traditional uses of plants, involving an interviewed sample of 66 informants. Fifty-eight of them (87.9%) listed a total of 39 species used as ethno-veterinary and/or fodder plants. Ten ethno-veterinary species (28 citations) were reported by 20 informants as used to treat diseases commonly affecting animals in the studied area, namely respiratory tract problems (Laphangium luteoalbum, Gyrocarpus americanus, Craibia brevicaudata subsp. baptistarum, Lepisanthes senegalensis, Ptaeroxylon obliquum, Ximenia americana) and skin diseases and wounds (Aloe littoralis, Blepharis sp., Ficus thonningii), or acting as a general tonic (Faidherbia albida). Thirty-four plants (235 citations) were cited by 58 informants as fodder. In this category of use, the most cited species were Terminalia prunioides (30 citations), Faidherbia albida (28 citations) and Spirostachys africana (21 citations). Our study shows that communities living in South Angola Mopane woodlands still retain a valuable traditional knowledge about plants used to maintain animal health and welfare. This body of knowledge and related skills can play a crucial role in the resilience of livestock systems facing present environmental and socioeconomic changes.